2009
DOI: 10.1093/eurheartj/ehp014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal management patterns and outcomes of non-ST elevation acute coronary syndromes in patients with kidney dysfunction

Abstract: Despite temporal increases in invasive management of NSTE-ACS, patients with kidney dysfunction are more commonly treated conservatively, with an associated worse outcome. In-hospital revascularization was independently associated with improved survival, irrespective of eGFR. Randomized controlled trials involving patients with kidney dysfunction are needed to confirm whether more aggressive treatment will improve their poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
55
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 35 publications
12
55
1
Order By: Relevance
“…Our analysis found that MI patients differ in their clinical and angiographic characteristics, depending on their IRF grade, consistent with the findings of other studies [5][6][7][8][12][13][14][15][16]. In patients with worse IRF, there is a greater percentage of predictors of poorer prognosis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our analysis found that MI patients differ in their clinical and angiographic characteristics, depending on their IRF grade, consistent with the findings of other studies [5][6][7][8][12][13][14][15][16]. In patients with worse IRF, there is a greater percentage of predictors of poorer prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…The populations of patients with particular IRF grades noted in our analysis are comparable with the data from the GRACE [5], ACS I/II [5], and SWEDEHEART [7] registries. The observed differences between the studies result from the adopted definitions of renal dysfunction and criteria use to select and stratify the analysed population.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…21 The pathophysiology in ACS patients with underlying renal dysfunction has been studied 22 Lesions in the coronaries of patients with renal dysfunction were found to be longer with more luminal encroachment and have higher plaque burden compared to coronaries of non renal dysfunction patients. Coronary plaque composition assessed with radio frequency IVUS depicted greater necrotic core with dense calcium and less fibrous tissue, all these changes make the coronary plaque less stable.…”
Section: Discussionmentioning
confidence: 99%